Registration of 'Acala 1517‐16 B2RF', a New Acala Cotton Cultivar with Insect and Herbicide Resistance. Issue 3 (30th August 2016) - Zhang, Jinfa; Flynn, Robert; Hughs, Sidney E.; Jones, Don C.
Abstract : Insect pests and weeds cause significant yield losses in cotton ( Gossypium hirsutum L.) production. The New Mexico Agricultural Experiment Station announces the release of an insect‐resistant and glyphosate herbicide‐tolerant Acala cotton cultivar, 'Acala 1517‐16 B2RF' (Reg. No. CV‐133, PI 678370), possessing Bollguard II (BGII or B2) and Roundup‐Ready Flex (RF) traits. Cotton with the B2 trait has an excellent season‐long in‐plant protection against pink bollworm [ Pectinophora gossypiella (Saund.)], tobacco budworm ( Heliothis virescens F.), American bollworm [ Helicoverpa armigera (Hubner)], and glyphosate and an improved resistance to beet armyworm [ Spodoptera exigua (Hübner)], soybean looper ( Pseudoplusia includens Walker), and bollworm ( H. zea Boddie). The new cultivar was selected as a progeny row derived from a backcross BC3 F3 between a Monsanto B2RF donor and NM 970123 as the recurrent parent. Acala 1517‐16 B2RF was tested in 11 replicated field trials in New Mexico from 2007 to 2009, one field test in the High Plains of Texas, and nine locations outside of the Southwest region in 2009. Acala 1517‐16 B2RF had similar lint yield to 'Acala 1517‐99W' containing two Bt genes and two conventional cultivars 'Acala 1517‐08' and 'PHY 72 Acala'. The most improved trait was its greater boll weight. In general, Acala 1517‐16 B2RF had similar fiber quality to the three checks in most of the tests, but its fibers were coarser than Acala 1517‐99W and finer than Acala 1517‐08 and PHY 72 Acala. This insect‐resistant and glyphosate‐tolerant Acala cotton cultivar is best adapted to the U.S. Southwest arid region of the Cotton Belt, where conventional Acala 1517 cultivars are grown.